Baroreflex Impairment Precedes Cardiometabolic Dysfunction in an Experimental Model of Metabolic Syndrome: Role of Inflammation and Oxidative Stress - Bernardes, Nathalia (2018)
This study analyzes whether autonomic dysfunction precedes cardiometabolic alterations in spontaneously hypertensive rats (SHR) with fructose overload. Animals were randomly distributed into three groups: control, hypertensive and hypertensive with fructose overload. Fructose overload (100 g/L) was initiated at 30 days old, and the animals (n = 6/group/time) were evaluated after 7, 15, 30 and 60 days of fructose consumption. Fructose consumption reduced baroreflex sensitivity by day 7, and still induced a progressive reduction in baroreflex sensitivity over the time. Fructose consumption also increased TNFα and IL-6 levels in the adipose tissue and IL-1β levels in the spleen at days 15 and 30. Fructose consumption also reduced plasmatic nitrites (day 15 and 30) and superoxide dismutase activity (day 15 and 60), but increased hydrogen peroxide (day 30 and 60), lipid peroxidation and protein oxidation (day 60). Fructose consumption increased arterial pressure at day 30 (8%) and 60 (11%). Fructose consumption also induced a late insulin resistance at day 60, but did not affect glucose levels. In conclusion, the results show that baroreflex sensitivity impairment precedes inflammatory and oxidative stress disorders, probably by inducing hemodynamic and metabolic dysfunctions observed in metabolic syndrome.